“Digital” and sovereignty in modern Russian educational policy - Afanasyeva, Kristina A. (Izvestiya of Saratov University. Sociology. Politology, 2024)
The article presents an analysis of the contradiction that todaycharacterizes the stateinitiative for the transition of Russian education from the Bologna format to “sovereign” and “unique” functioning. This is a contradiction between the plans for accelerated digitalization of the educational sphere and, at the same time, for it to acquire certain qualities that are unique nowhere else in the modern world. Arguments are given in favor of the fact that attempts by subjects of Russian educational policy to give constructive meaning to the ideas of sovereignty of education in our country and its achievement of a state of uniqueness will face the objective need to sacrifice sovereignty and uniqueness for the sake of fulfilling the technical conditions of digitalization. The article predicts the expected risky consequences of such a conflict of meanings and goals in the ideology of planned educational reforms for state educational policy.